(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The paper proposes an new approach of enhancing the linearity of metal-insulator-ferroelectric-gate (MIFG) MOS transistor-based subthreshold operational transconductance amplifiers (OTAs). Using the ferroelectric gate material, one of the distinctive features of MIFG MOS transistors, this method improves OTA performance without compromising energy efficiency. Through theoretical modeling and simulation investigations, the proposed linearized subthreshold OTA architecture is investigated. Nonlinearity compensation techniques have been developed, enhancing linearity in the subthreshold area over a wide range of input signal amplitudes. In addition, the investigation examines into design elements influence overall linearity and power consumption. Enticing applications for such linearized subthreshold OTA encompass sensor interfaces, battery-operated devices, and ultra-low-power analog signal processing.